ANALISIS PEMASARAN DAN PENDAPATAN NELAYAN JARING INSANG (Gill Net) DI DESA REBAQ RINDING KECAMATAN MUARA MUNTAI KABUPATEN KUTAI KARTANEGARA - Al Hamdani; Helminuddin; Said Abdusysyahid (Jurnal Pembangunan Perikanan dan Agribisnis, 2019)
The research aims to 1) analyze marketing margins, marketing efficiency and farmer's share of gillnet fishing businesses in Rebaq Rinding Village; 2) analyze the income of the fishers who use gillnet method in Rebaq Rinding Village. The sample method used is the purposive sampling method for the respondent of gillnet fishers and snowball sampling method for the respondent of the fish collectors. Data analysis methods used are marketing margin analysis, marketing efficiency, farmer's share and fishermen's income analysis. The results of the study showed that the marketing margin at the one-level marketing channel for snakehead murrel fish is Rp. 10,000/Kg, sucker barb fish Rp. 8,500/Kg, glass fish Rp. 11,000/kg, kissing gourami fish Rp. 12,000/Kg. The two-level marketing channel for snakehead murrel fish is Rp. 30,000/Kg, sucker barb fish Rp. 11,000/kg, glass fish Rp. 11,500/Kg, kissing gourami fish Rp. 21,000/Kg, with a total margin on one level marketing channel of Rp. 41,500/Kg and a two-level marketing channel of Rp. 73,500/Kg. More efficient marketing is on the one level marketing channel for snakehead murrel fish of 54.5%, sucker barb fish 29.2%, glass fish 26.7%, kissing gourami fish 29.4%. Farmer’s share is obtained from the results of analysis found in the two-tier marketing channel for snakehead murrel fish of 25%, sucker barb fish 21.4%, glass fish 23.3%, kissing gourami fish 16%. The income of gillnet fishers in Rebaq Rinding Village with an average value of Rp. 3,003,216/month.